2019
DOI: 10.3389/fimmu.2019.00063
|View full text |Cite
|
Sign up to set email alerts
|

Humanized Mice Reveal New Insights Into the Thymic Selection of Human Autoreactive CD8+ T Cells

Abstract: Thymic selection constitutes the first checkpoint in T-cell development to purge autoreactive T cells. Most of our understanding of this process comes from animal models because of the challenges of studying thymopoiesis and how T cell receptor (TCR) specificity impacts thymocyte phenotype in humans. We developed a humanized mouse model involving the introduction of autoreactive TCRs and cognate autoantigens that enables the analysis of selection of human T cells in human thymic tissue in vivo. Here, we descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 47 publications
2
20
0
Order By: Relevance
“…We detected a MART1 TCR dim population in the periphery of mice that was similar between mice regardless of transplanted thymus. Such populations have been observed previously in TCR transgenic mouse and humanized mouse models, and have been shown by antibody staining or sequencing to express multiple TCRα chains. Our observation that MART1 TCR dim cells have similar CD3 expression as MART1 TCR bright cells, indicating similar expression of surface TCR but reduced expression of tetramer‐stainable MART1 TCRs, suggests a similar phenomenon is taking place in our system.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…We detected a MART1 TCR dim population in the periphery of mice that was similar between mice regardless of transplanted thymus. Such populations have been observed previously in TCR transgenic mouse and humanized mouse models, and have been shown by antibody staining or sequencing to express multiple TCRα chains. Our observation that MART1 TCR dim cells have similar CD3 expression as MART1 TCR bright cells, indicating similar expression of surface TCR but reduced expression of tetramer‐stainable MART1 TCRs, suggests a similar phenomenon is taking place in our system.…”
Section: Discussionsupporting
confidence: 60%
“…We examined MART1 TCR dim and MART1 TCR bright cells and found that they had similar CD3 expression, as shown in Figure S5a‐c. Because TCR and CD3 are expressed on the surface of T cells with a well‐described stoichiometry, the fact that MART1 TCR dim cells showed reduced MART1 TCR expression with unchanged CD3 expression suggests that these T cells may express endogenously rearranged TCRα chains, which has been previously observed in murine and humanized mouse transgenic TCR systems, and in ordinary humanized mouse models, where 10% of normal human thymocytes selected in a human thymus graft expressed multiple TCRα chains . MART1 TCR dim cells were present in similar proportions among both GFP + CD4 + and CD8 + cells (Figure S5e) and as a proportion of splenocytes (Figure S5f) regardless of selecting thymus.…”
Section: Resultsmentioning
confidence: 59%
See 1 more Smart Citation
“…A recent study specifically investigated the ability of human thymic APCs to promote negative selection of CD8 T cells. To do so, BLT hu-mice were transplanted with a mix of human CD34 + HSCs: some were transduced with vectors encoding either a MART1 or a control antigen, while others were transduced with a TCR specific for a MART1 peptide in the context of HLA-A2 [ 98 ]. In these animals, T cells expressing the MART1-specific TCR developed among other T cells and in the presence of APCs that either did or did not express the MART1 peptide.…”
Section: Using His Mice To Study Tolerance and Autoimmunitymentioning
confidence: 99%
“…Human immune system (HIS) mice have been highly instrumental for in vivo studies of human immune function and immune disorders. The HIS mouse was the first model that made it possible to study human immune responses in real time in vivo under physiologic or pathogenic conditions, such as HIV pathogenesis ( 1 ), human xeno-immune responses ( 2 ), complex interplay between hypercholesterolemia and human adaptive immunity ( 3 ), and intrathymic selections of human T cells ( 4 ). HIS mice, conjunct with tissue chimeras (i.e., with organ repopulation by human parenchymal cells), were found highly valuable in elucidating immunopathology of human-tropic viral infections, such as hepatitis B and hepatitis C viruses ( 5 , 6 ) and respiratory viruses ( 7 ).…”
Section: Introductionmentioning
confidence: 99%